Aplicación Web para la evaluación y seguimiento de entregables académicos finales de aprendices del Centro de Servicios Financieros del Sena-AWESA (2021)
The development of Web applications in recent years has been increasing since companies are implementing technologies in their operational processes to be at a level more competitive, in addition to this, due to the pandemic many companies have incorporated tools that allow you to carry out your work remotely and thus centralize your operational processes and carry out a more effective follow-up of the fulfillment of activities assigned.